2020
DOI: 10.1111/ijfs.14923
|View full text |Cite
|
Sign up to set email alerts
|

Formation and emulsification properties of self‐assembled potato protein microgel particles under different pH conditions

Abstract: Formation and emulsification properties of potato protein microgel particles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…For instance, it has been reported that PoPM exhibits poor emulsifying property when the pH of the media is near their pI (4.5–5.0) while the PoPM-stabilized oil-in-water emulsions were found to be highly stable when the pH of the media is away from the pI. 27 Another report mentioned that the presence of salt enhanced the surface activity of PoP, and consequently, foamability and foam stability were altered. 56 Also, the LC droplets were found to be environment-sensitive, where a decrease in ionic strength and/or pH of the media caused a decrease in the percentage of LC droplets undergoing bipolar-to-radial transition, whilst the transition could only be obtained under specific pH and ionic strength conditions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, it has been reported that PoPM exhibits poor emulsifying property when the pH of the media is near their pI (4.5–5.0) while the PoPM-stabilized oil-in-water emulsions were found to be highly stable when the pH of the media is away from the pI. 27 Another report mentioned that the presence of salt enhanced the surface activity of PoP, and consequently, foamability and foam stability were altered. 56 Also, the LC droplets were found to be environment-sensitive, where a decrease in ionic strength and/or pH of the media caused a decrease in the percentage of LC droplets undergoing bipolar-to-radial transition, whilst the transition could only be obtained under specific pH and ionic strength conditions.…”
Section: Resultsmentioning
confidence: 99%
“…have prepared potato protein microgels (PoPM) by uncontrolled denaturation of the potato protein (PoP) and used them as Pickering stabilizers for corn oil-in-water emulsions. 27 However, there is currently a lack of in-depth understanding on the stabilization and mechanism of dynamic response in the LC droplets when stabilized by plant-based materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pH adjustment to various levels might cause denatured WPI molecules to undergo different aggregation modes, and formation of various nanogel particles. The higher negative charge on the protein surface at pH 6 might lead to the anisotropic growth of gel nanoparticles ( Liu et al, 2021 ). The microgel particles prepared at pH 4 had the largest particle size among the other samples, which can be related to the self-aggregation and a complex interplay between the molecules close to the isoelectric pH of denatured WPI ( Araiza Calahorra, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…HIPPE stabilized by protein microgel particles, under the factors of pH, ionic strength, and particle concentration, can influence the properties of emulsion droplet size, stability, microstructure, rheological properties, etc. [ 31 , 35 ]. At the same time, HIPPE stabilized by protein microgel particles has a great potential for wide application in food.…”
Section: Hippe Stabilized By Solid Particlementioning
confidence: 99%